2011
DOI: 10.3892/or.2011.1286
|View full text |Cite
|
Sign up to set email alerts
|

CDH12 promotes the invasion of salivary adenoid cystic carcinoma

Abstract: Abstract. cadherins are found in almost all living organisms. In addition to their role in the formation and maintenance of normal tissue architecture, cadherins seem to play a crucial role in the cell-cell interactions of cancer cells in tumorigenesis, invasion and metastasis. the aim of the present study was to identify the role of cDH12 in the invasion and metastasis of salivary adenoid cystic carcinoma (sAcc). real-time pcr results showed that cDH12 is abnormally expressed in the highly metastatic sAcc cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…CDH12 can promote the migration and invasion ability of salivary adenoid cystic carcinoma [11]. According to our findings, CDH12 may be an oncogene and promote the malignant progression of CRC cells.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…CDH12 can promote the migration and invasion ability of salivary adenoid cystic carcinoma [11]. According to our findings, CDH12 may be an oncogene and promote the malignant progression of CRC cells.…”
Section: Discussionmentioning
confidence: 56%
“…This indicates that CDH12 acts as a tumor suppressor gene in the non-small-cell lung cancer [10]. In addition, CDH12 is able to promote the migration and invasion ability of salivary adenoid cystic carcinoma [11]. However, the function of CDH12 in colorectal cancer is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, mQTL genes were also enriched in other cancer-related pathways. For example, five mQTL putative genes are part of the cadherin family, and at least two ( CHD12 and CHD13 ) have been broadly studied for their role in cancer (7274). Genes related to angiogenesis and vascular permeability pathways had also significant matches, and at least one of them ( NRP1 ) has been studied before in meningioma (49).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that expression levels of E-cadherin-catenin are positively correlated with the degree of SACC cell differentiation [13]. Wang JF et al found that N-cadherin was abnormally expressed in highly metastatic SACC tissue, promoting invasion and migration in SACC cells [14]. Although evidence on the relationship between cadherin family genes and SACC is increasing, the role of the cadherin-4 gene (CDH4) in SACC remains unknown.…”
Section: Introductionmentioning
confidence: 99%